Camera trapping and telemetry for detecting and quantifying animal interactions: Not anything goes - Cesar Herraiz; David Ferrer-Ferrando; Joaquín Vicente; Pelayo Acevedo (Ecological Indicators, 2024)
Telemetry using Global Positioning Systems (GPS) and camera trapping are two widely used approaches to detect animal interactions involving wildlife. However, while the former follows an individual-based approach, the latter follows a population-based approach, which may lead to different outcomes when describing interaction networks. In this study, we compared the performance of GPS telemetry, regular grid camera trapping (CT-RG), and resource monitoring camera trapping (in which cameras are placed monitoring a valuable resource for animals, such as water or food; CT-RM) in detecting and quantifying animal interactions. We used spatially explicit simulated trajectories of 150 individuals of 3 imaginary species. We simulated 9 different scenarios of resource visiting frequency and spatial resource aggregation in the environment to assess the potential influence of animal behavior and landscape structure. The simulated trajectories were sampled using the three approaches with six different sampling efforts each, and the direct and indirect interactions between the three species were quantified. Additionally, CT-RG and CT-RM were applied in Doñana National Park to evaluate their differences and limitations in field application. In terms of simulation, CT-RM offered the best performance in detecting direct interactions, and GPS achieved good performance when using a high number of fixes per hour. Both CT-RM and GPS also achieved good performance in detecting indirect interactions. CT-RG, on the other hand, missed most direct and indirect interactions, but correctly identified the pairs of species that interacted indirectly at some point. In the field trial, CT-RM and CT-RG detected almost the same number of species pairs interacting indirectly. However, CT-RG missed at least half of the species pairs that interacted directly. The spatial aggregation of the resource favors the performance of GPS over CT-RM, while the opposite occurs when the frequency of animal visits to the resource increases. To summarize, CT-RM is the most reliable method for detecting interactions when resource monitoring is feasible (e.g., small ponds in arid areas). Otherwise, GPS may show better performance, although it may miss direct interactions if a high fix rate is not used. Finally, the use of CT-RG should be limited to identify which species could potentially interact indirectly, but not to quantify these interactions.